Embedding Monodisperse LaOx Into Pt Nanoclusters for Ultra‐Stable and Efficient Hydrogen Isotope Oxidation - Guilin Wei; Jiangfeng Song; Yan Shi; Linsen Zhou; Xianglin Wang; Junhong Luo; Ning Liu; Feize Li; Xingwen Feng (Advanced Science)
Abstract Catalytic oxidation plays a crucial role in the efficient treatment of hydrogen isotopes, with the key technical challenge being the development of high‐performance catalysts to enhance isotope removal efficiency, thereby reducing environmental pollution and ensuring public radiation safety. Herein, the strategic control of platinum nanoclusters confined within silicalite‐1 zeolites is reported to enhance the high removal efficiency for hydrogen isotopes under low‐temperature conditions for the first time. Incorporating a single lanthanum oxide (LaOx) into Pt nanoclusters adapts the local charge of adjacent Pt atoms, significantly altering their electronic structure. The existence of individual LaOx species is confirmed by X‐ray absorption spectroscopy and aberration‐corrected electron microscopy, and the performance enhancement mechanism is further probed by theoretical calculations. This embedded single LaOx both facilitates local charge adjustment and supplies abundant active oxygen species, leading to performance enhancement by reducing the energy barrier of rate‐determining step (O* + H → OH*), in accordance with the Mars‐van Krevelen mechanism. Consequently, during a surprisingly long‐term restart performance test (≈267 d), the PtLaOx@S‐1 maintained a high conversion rate over 99% at 50 °C and a space velocity of 48,000 mL·g−1·h−1. This study highlights the potential of individual LaOx sites for enhancing hydrogen isotope oxidation.